Tiesu varas amatpersonu pamattiesību ierobežojums kā taisnīgas tiesas garants - Simsons, Toms (Latvijas Universitāte, 2019)
Darbs sastāv no ievada, trim nodaļām un secinājumiem. Darba pirmajā nodaļā apskatīts varas dalīsanas princips kā pamats tiesu varas neatkarībai. Otrajā nodaļā - likumos noteiktās prasības un ierobežojumi tiesu varas amatpersonām. Trešajā nodaļā analizēts tiesu varas amatpersonu biedrošanās tiesību, tiesību brīvi izvēlēties nodarbošanos un privātās dzīves neaizskaramības ierobežojums. Mērķis ir vērtēt likumos noteiktos tiesu varas amatpersonu ierobežojumus no cilvēka pamattiesību aspekta. Secināts, ka pamattiesību ierobežojums tiesu varas amatpersonām ir samērīgs un pamatots, kalpo sabiedrības interesēm un ir garants taisnīgai tiesai. Atzīmētas dažas nepilnības normatīvajā regulējumā un sniegri ieteikumi uzlabošanai.

The work consists of an introduction, three chapters and conclusions. The first chapter deals with the principle of separation of powers as a basis for the independence of the judiciary. In the second chapter, the requirements and restrictions imposed by law on judicial officials. The third chapter analyses the right of association of judicial officials, the right to choose occupation freely and the limitation of privacy. The aim is to assess the restrictions imposed by law on judicial officials from the fundamental human rights aspect. It is concluded that the restriction of fundamental rights to judicial officers is proportionate and justified, serves the public interest and guarantees a fair trial. Some shortcomings in the regulatory framework and safety recommendations for improvement are noted.
Restriction of the fundamental rights of judical officers as a guarantee of a fair trial
Keywords: Juridiskā zinātne; Tiesu vara; Tiesu varas amatpersonas; Cilvēku pamattiesības; Pamattiesību ierobežojums; Taisnīga tiesa